The consequences of the Brexit vote on management attitudes to recruitment in the hospitality industry - Ferris, Katy; Cameron, Derek; Jenkins, Andrew; Marson, James (Kluwer Law International, 2018)
This article investigates the perceptions of managers in the hospitality industry to the Brexit vote and its implications for their recruitment strategies. A survey instrument was used to ascertain perceptions of challenges and opportunities around key themes including current recruitment; the implications of removal of free movement principles on immigration, employment and retention; the effects of the decision on salaries, supplier contracts and renegotiations, and its effects of non-national staff. The article presents the findings of the surveys and offers suggestions as to issues the Brexit negotiating team might take into consideration when determining the British withdrawal strategy.